About one extremal problem for open sets and partially non-overlapping domains - Targonskii, A.L.; Targonskaya, I.I.; Vashenko, K. (Український математичний вісник, 2019)
Sharp estimates of a product of the inner radii for pairwise disjoint domains are obtained. In particular, we solve an extremal problem in the case of any finite number of free poles on the rays.